2007
DOI: 10.1111/j.1524-4725.2007.33008.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Dynamic Telepathology in the Mohs Surgery Laboratory Utilizing iChat AV Videoconferencing Software

Abstract: Dynamic telepathology can be accomplished accurately and inexpensively by use of readily available consumer products and software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The study found complete concordance between telepathology and conventional light microscopy for all 110 slides, underscoring the accuracy of telepathology [ 12 ]. Further validation came from a study utilizing iChat AV video conferencing for real-time transmission of histologic images and audio from a MMS lab to a remote dermatopathologist [ 16 ]. This setup, compatible with Apple Macintosh platforms, allowed for immediate consultation.…”
Section: Teledermatology and Mmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found complete concordance between telepathology and conventional light microscopy for all 110 slides, underscoring the accuracy of telepathology [ 12 ]. Further validation came from a study utilizing iChat AV video conferencing for real-time transmission of histologic images and audio from a MMS lab to a remote dermatopathologist [ 16 ]. This setup, compatible with Apple Macintosh platforms, allowed for immediate consultation.…”
Section: Teledermatology and Mmsmentioning
confidence: 99%
“…There was a 95% (19/20) agreement in tumor diagnosis between dynamic telepathology and conventional microscopy, and a 100% agreement for all 20 Mohs frozen section consultations. The ability of this system to capture and transmit both video and audio was crucial in ensuring high-quality, accurate histologic evaluations and effective communication between the surgeon and the dermatopathologist [ 16 ]. Additionally, telepathology has practical applications in urban settings where it overcomes logistical challenges like specimen transport delays, as highlighted by Nehal and colleagues [ 12 ].…”
Section: Teledermatology and Mmsmentioning
confidence: 99%
“…The video codecs involved introduce large delays in order to match the bandwidth limitations in conventional home consumer networks, which can often transfer less than 1 Mbps. Examples are the iChat software [42] or its successor Facetime, which implements the well-known H.264 standard [31], or Skype [50]. In that context it is mainly the large compression delay of several hundred milliseconds [32] which prevents conventional AV-conferencing systems from being applied in network music performances.…”
Section: Low-latency Videomentioning
confidence: 99%
“…In addition, they might be adjusted to a panel of distinct aims. These include performance of primary diagnosis at potentially multiple places separated from tissue examination, processing and image acquisition from glass slides (frozen section service), confirmation, refinement of primary diagnoses (secondary diagnoses and diagnostic quality assurance by expert consultation), teaching and education of students and young colleagues (e-learning, education, and training), and on-line (live) teleconferencing [15-17]. …”
Section: Introductionmentioning
confidence: 99%